Initial Paper Assignment for Philosophy 167. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Initial assignment for a short (2-3) page paper. Think of this exercise as an initial attempt to state the evidence problem posed by the three "chief world systems" as understood in 1600.